2019
DOI: 10.1108/medar-11-2018-0390
|View full text |Cite
|
Sign up to set email alerts
|

Corporate tax planning and corporate tax disclosure

Abstract: Purpose This paper aims to examine the impact of corporate tax planning (TP) on tax disclosure (TD). Using tax expenses data set, with the detailed effective tax rate (ETR) by reconciling individual items of income and expenses. Design/methodology/approach A firm-level panel data set is used to analyse 286 non-financial listed companies on Bursa Malaysia that spans the period 2010-2012. Multivariate statistical analyses were run on the sample data. The empirical understanding of TD depends on public sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 83 publications
1
8
0
13
Order By: Relevance
“…year of publication, study quality), so, we eliminated some of them depending on study quality. In several cases, articles with titles or abstracts containing any combination of the search terms addressing themes other than corporate entrepreneurship and were excluded from the sample (Mgammal, 2019). At the same time, articles addressing aspects of corporate entrepreneurship (e.g.…”
Section: A Conceptual Viewmentioning
confidence: 99%
“…year of publication, study quality), so, we eliminated some of them depending on study quality. In several cases, articles with titles or abstracts containing any combination of the search terms addressing themes other than corporate entrepreneurship and were excluded from the sample (Mgammal, 2019). At the same time, articles addressing aspects of corporate entrepreneurship (e.g.…”
Section: A Conceptual Viewmentioning
confidence: 99%
“…The relationship between the effectiveness of tax audits, tax laws, and the use of specialized information system tools, the use of information system tools can be activated. The results showed that tax auditors can track tax violations correctly, and better tax auditor training in the use of information systems [20,21]. Other studies are factors that influence the effectiveness of tax audits in Tanzania, the research findings indicate that there are five main important factors for the effectiveness of tax audits; i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hoffman's tax planning theory discusses that management has the incentives to legally avoid paying corporate taxes in order to increase the distributable profits. Profitability is a widely used indicator to measure performance [56]. According to this theory, tax planning activities are desirable when it is possible to minimise the taxable income without jeopardizing the accounting income.…”
Section: Corporate Tax Avoidance and Earnings Managementmentioning
confidence: 99%